Measuring Usability using USE Questionnaire in the MyTelkomsel Application - Salsabila, Alya Putri; Ibrahim Anwar, Setiady; Mulia Lasardi, Ekky; Fami, Amata; RG Barus, Irma (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
The MyTelkomsel application is one of Indonesia's most popular cellular provider applications. Telkomsel established it to provide convenience for customers in managing their telecommunications services. As the MyTelkomsel application runs, few users complain about the shortcomings of the MyTelkomsel application features, which are considered less than optimal, such as a very long application response, an unsatisfactory UI display, and so on. Therefore, the author researched usability calculations on the MyTelkomsel application through the USE Questionnaire approach with the main focus on the five usability measurement criteria: Learnability, Efficiency, memorability, errors, and Satisfaction. This study used SPSS and Google Spreadsheets to analyze these variables, with 35 respondents. The results showed that the five criteria used in measuring Usability obtained results with a feasibility level for the Learnability aspect of 83.71%, Efficiency of 81.71%, and Satisfaction of 81.28% with a very feasible category. Memorability aspects amounted to 77.14%, and Errors amounted to 72%, with a decent category. The overall usability analysis results obtained a percentage value of 79.17% with a decent category.